Sistem Informasi Geografis Pada Kelompok Wanita Tani Berbasis Data Object - Rima Maulini; Oki Arifin; Dwirgo Sahlinal; Kurniawan Saputra (Jurnal Teknologi Informasi dan Terapan, 2021)
Geographical Information System technology (GIS) uses a document database (JSON) as an object that can be applied to geographic information systems using object data in the group of women farmers (KWT) in Lampung Province. The distribution of KWT in Lampung Province can be done using a geographic information system. The use of relational databases can be replaced by using the document database as a database on the distribution of KWT in Lampung Province. There are 3 data markers for example KWT in Lampung province using google maps. By using a JSON document as a document database as an object it is possible to serve as a geographic information system database.